Modification of a pencil graphite electrode with halloysite and gold–palladium bimetallic nanoparticles for diclofenac sodium determination - Mahdi Ozgoli; Behjat Deiminiat; Ehsan Moradi; Gholam Hossein Rounaghi (Scientific Reports)
Abstract This paper describes a new, simple, cheap, and accurate electrochemical sensor for measuring the concentration of diclofenac in solutions. The surface of a pencil graphite electrode (PGE) was modified with halloysite film, and decorated with gold–palladium bimetallic nanoparticles (Au–PdNPs) to fabricate the sensor. Cyclic voltammetric technique was employed to deposit Au–PdNPs on the surface of halloysite modified PGE. Field emission scanning electron microscopy (FE-SEM), energy dispersive spectroscopy (EDS) and electrochemical impedance spectroscopy (EIS) were used to study the surface changes of the pencil graphite electrode during the modification process. The electrochemical behavior of the fabricated Au–PdNPs/halloysite/PGE was evaluated for diclofenac sodium determination using cyclic voltammetry (CV) and differential pulse voltammetry (DPV) techniques. The effect of the parameters controlling the electroanalytical performance of the fabricated sensor was examined and optimized. The developed sensor exhibited an excellent catalytic activity for the electrooxidation of diclofenac molecules in aqueous solutions. It also showed a high selectivity for diclofenac molecules in the presence of interfering species. Moreover, the reproducibility (RSD 2.45%), repeatability (RSD 2.97%), and stability (reduction 4.7%) of the proposed sensor were satisfactory. In addition, the oxidation peak current of diclofenac was linear in the range of 1–100 µM, with a detection limit of 0.047 µM with respect to the concentration of diclofenac. The applicability of the prepared sensor was proved by measuring the concentration of diclofenac in real samples, and satisfactory results were obtained in all experiments.